Investigations into the urinary tract - Smee, Nicole (Kansas State University, 2012)
A urinary tract infection (UTI) is defined as a temporary or permanent breach in host defense mechanisms that allows microbes to adhere, multiply, and persist within the urinary tract. Development of a UTI is multi-factorial with bacterial number and virulence and the health status of the patient (normal urogenital tract anatomy and physiology and systemic immunocompetence) playing important roles in determining the outcome. A UTI can involve a single site, such as the renal pelvis, ureter, bladder, urethra, prostate or vagina, or can include multiple sites. Infection of any portion of the urinary tract may increase the likelihood of infection in other locations. Diagnosis of a UTI incorporates findings from the history, physical examination, complete urinalysis, and urine culture. Proper classification and localization of the UTI are important when formulating a treatment regime as well as evaluating treatment success and failure. Most UTI can be successfully managed with appropriate antibiotic treatment; however, bacterial resistance and compromised host defense mechanisms can result in persistent or recurrent infections. In patients with recurrent UTI, identification of underlying predisposing conditions will often improve treatment success. In patients where underlying causes cannot be identified or treated, therapies designed to prevent recurrent UTI may be employed. Proanthrocyanidins found in cranberry juice inhibit E. coli attachment to human uroepithelial cells, impairing bacterial adherence and colonization. These characteristics have encouraged widespread usage of cranberry extract as a prevention strategy for woman predisposed to urinary tract infections. E. coli is a common cause of canine urinary tract infection. Current treatment emphasizes eradication of established infection rather than infection prevention, but increased antibiotic resistance necessitates strategies to prevent infection. We hypothesized that purified cranberry extract (CE) inhibits bacterial adhesion to canine uroepithelial cells. The results of our study show that CE supplementation can reduce adhesion of uropathogenic E. coli to canine uroepithelium and suggests one mechanism by which CE might improve urinary tract health.
Keywords: Urinary Tract Infection; Enzymuria; Cranberry; Veterinary Medicine (0778)